Clinical Outcomes, Contrast Sensitivity, Reading Performance and Patient Satisfaction Following Bilateral Implantation of AT LARA 829MP EDoF IOLs - Ganesh S (Dove Medical Press, 2021)
Sri Ganesh, Sheetal Brar, Nikhil RP, Dishitha Rathod Department of Phaco-Refractive Surgery, Nethradhama Super Speciality Eye Hospital, Bangalore, Karnataka, IndiaCorrespondence: Sheetal BrarNethradhama Superspeciality Eye Hospital, 256/14, Kanakapura Main Road, 7th Block, Jayanagar, Bengaluru, Karnataka, 560070, IndiaTel +919591002092Email brar_sheetal@yahoo.co.inPurpose: To evaluate the visual outcomes, contrast sensitivity, reading performance and patient satisfaction after bilateral implantation of AT LARA extended depth of focus (EDoF) intraocular lenses (IOLs).Methods: Patients undergoing phacoemulsification for age-related cataract and satisfying the eligibility criteria underwent bilateral implantation with AT LARA EDoF IOLs (Carl Zeiss Meditec, Jena, Germany). At follow-up visits of 1, 3, 6 and 12 months, binocular uncorrected and corrected distance, intermediate and near visual acuity, reading performance, defocus curve, contrast sensitivity and patient satisfaction for dysphotopsia and spectacle independence were evaluated.Results: A total of 60 eyes from 30 patients with a mean age of 65.40± 7.71 years were included in the study. At 12 months, 83% of patients (n=25) had binocular cumulative uncorrected distance visual acuity (UDVA) of 20/20 or better. Postoperative spherical equivalent refraction accuracy was within ± 0.50 D for 95% of eyes (n=57) and refractive cylinder accuracy was within ≤ 0.50 D in 95% of eyes (n=57). The mean binocular uncorrected near visual acuity (UNVA) was 0.16± 0.09 logMAR, and the mean uncorrected intermediate visual acuity (UIVA) at 60 and 80 cm was 0.01± 0.09 and 0.03± 0.08 logMAR, respectively, at 12 months. Reading speeds at 40, 60 and 80 cm showed improvement over time. No patient had complaints of severe dysphotopsia and none of the patients required glasses for any activity. No eye underwent YAG-laser capsulotomy for significant posterior capsule opacification at the end of mean follow-up.Conclusion: In our limited experience of 30 patients at 12 months, AT LARA EDoF IOLs resulted in excellent visual outcomes for uncorrected distance, intermediate and near visual acuity. The incidence of dysphotopsia and spectacle dependence was low, resulting in good patient satisfaction.Trial Registry: CTRI/2020/08/027105 (www.ctri.nic.in).Keywords: AT LARA, extended depth of focus, EDoF IOL, spectacle independence